Children's emotional and behavioral problems in the shadow of terrorism: The case of Israel. (February 2018) - Shechory Bitton, Mally; Laufer, Avital
Abstract: This research investigates the well-being of children subjected to prolonged exposure to missile attacks. A study of post-traumatic symptoms, emotional stress, and behavioral problems among 152 children from southern Israel, an area prone to missile attacks, was conducted. Post-traumatic symptoms were assessed by a self-reported version of the Post-traumatic Stress Disorder Reaction Index for Children (CPTS-RI). Emotional and behavioral problems were assessed by the Child Behavioral Checklist (CBCL), which was completed by the children's mothers. The mothers were asked to answer the CBCL regarding their children's behavior both in the present and prior to the missile attacks. CBCL results were then compared with those of comparable children (n = 125) living in central Israel who were not exposed to missile attacks and whose mothers were asked to answer a similar questionnaire. The results indicated that prolonged exposure to security threats did not result in high levels of posttraumatic symptoms. However, according to the mothers the emotional and behavioral states of the children deteriorated. This was found also when their current emotional and behavioral state was compared to similar children in central Israel. The complex effect of prolonged exposure to security threats is discussed.